Sexuality, sexual health and older people: A systematic review of research on the knowledge and attitudes of health professionals. (May 2016) - Haesler, Emily; Bauer, Michael; Fetherstonhaugh, Deirdre
Abstract: Objectives: Sexuality remains important to older people and should be recognised as an important part of their overall care. However, this appears to be poorly understood and addressed by many healthcare professionals. This systematic review reports on knowledge and attitudes of health professionals towards sexuality and sexual health of older people, including factors that impact knowledge and perceptions. Review methods and data sources: The review, conducted using Joanna Briggs Institute methods, included 23 studies of varied methodology published between January 2004 and January 2015. Results: Findings indicated that healthcare professionals often consider older people's sexuality as outside their scope of practice and there is lack of knowledge and confidence in this area. Cultural norms and taboos, length of time spent working with older people, familiarity with the older person, previous training and degree of exposure to people who are not heterosexual were all identified as factors that impact knowledge and attitude. Conclusions: Better role modelling and education are needed to improve knowledge and attitudes toward later life sexuality. Highlights: The review identifies the factors impacting on health professionals' knowledge and attitudes toward older people's sexuality and sexual health. Aged care workers often perceive the address of sexuality to be beyond their scope of practice. Improved education on the topic of sexuality in later life is imperative for all healthcare professions.